Controlled atmosphere as cold chain support for extending postharvest life in cabbage - Gage, Ewan; Jain, Ritika; Terry, Leon A.; Falagán, Natalia (Elsevier, 2024)
Postharvest management of cabbage relies on high-intensity cooling to control postharvest physiology, minimising quality loss despite incurring significant energy and environmental costs. As an alternative, we hypothesised that controlled atmosphere (CA) could allow increased storage temperature by supporting physiological regulation, while maintaining quality and reducing energy demand. This study examined the effect CA (1.5 kPa CO2 and 6 kPa O2) at 5 or 10 °C on cabbage quality, with the aim of proposing a more sustainable and resilient supply chain. CA treatment was effective at reducing head respiration at higher temperature, with CA/10 °C treatment achieving lower respiration rates than Control/5 °C. Improved head colour retention and maintenance of stump quality were observed in cabbage under CA conditions. CA effects were seen also at a regulatory level; CA promoted an average of 25.4% reduction in abscisic acid accumulation potentially as part of a wider hypoxia stress response and was successful in decreasing expression of the senescence-coordinating transcription factor BoORE15. This finding was linked with a lower in downstream expression of pheophytinase and subtilisin protease. These results demonstrated that CA treatment fundamentally modified postharvest physiology in cabbage, which can be exploited to enable storage at warmer temperatures, contributing to supply chains with lower energy demand and its associated environmental benefits.
Keywords: Brassica oleracea; Chlorophyll; Storage temperature; Hypoxic stress; ORE15; Pheophytinase; Subtilisin protease; 3108 Plant Biology; 31 Biological Sciences; 7 Affordable and Clean Energy; Plant Biology & Botany